Mapping Thickness and Maturity Level Of Peat in The Simpang Wie Village, East-Langsa Sub-district, Langsa City - berutu, prekdisampangate; Iswahyudi; Siregar, Dolly S. (Talenta Publisher, 2020)
Food needs become increasingly urgent along with the growth of populations. Indonesian particularly needs more land to be used or utilized to increase food productivity and to create field-work.This view is considered because of the decreasing mineral lands in Indonesian. By conducting a study on the mapping of the thickness and maturity level of peat, it can provide the usage of peatland regarding cultivated land. The result of mapping can appropriately be used to design land utilization and model of production system. This study was carried out at Simpang Wie Village, East-Langsa Sub-district, Langsa City, as known which is known as one of the Peatland areas in Langsa City. The study was conducted in December 2019. Survey method design was employed in this research while the research location was determined purposively, which means that it is directly chosen or purposively chosen because the location is a peatland. Data types applied by field observation in this study were primary and secondary data. In this study, This research requires four main following phases; (1)Preparation (2)Preliminary-Survey (3) Field-Implementation, and (4) Data Analysis/ Discussion. The research result shows that the peatland area width of 4.94 9 (Ha) was classified into two types peat thickness: Shallow/Thin Peat with thickness > 40-100 cm (1.95 Ha), and Moderate Peat with thickness of 101-195 cm (2.99 Ha). Based on the observation, the maturity Level of Peat also classified into two maturity levels, those are Hemic Maturity Level and Sapric Maturity Level. Therefore, the use of peatland area according to thickness and maturity level concluded that the thickness of 40-100 cm can appropriately be used to cultivate paddy-fields, palawijas and plantation crops (horticulture). Besides, the thickness of 101-195 cm can appropriately be used to cultivate plantation crops (horticulture), vegetable crops (olericulture), and fruit crops (fruticulture). At least, this land is suitable to be used for agricultural cultivation because it has hemic and sapric maturity level. Key words: peat, thickness, maturity level , hemic, sapric, cultivated land